“I’m pretty sure that we will win!”: The influence of score-related nonverbal behavioral changes on the confidence in winning a basketball game - Furley, Philip; Schweizer, Geoffrey (Journal of sport & exercise psychology, 2014)
The goal of the present research was to test whether score-related changes in opponents’ nonverbal behavior influence athletes’ confidence in beating their opponents. In an experiment, 40 participants who were experienced basketball players watched brief video clips depicting athletes’ nonverbal behavior. Video clips were not artificially created, but showed naturally occurring behavior. Participants indicated how confident they were in beating the presented athletes in a hypothetical scenario. Results indicated that participants’ confidence estimations were influenced by opponents’ score-related nonverbal behavior. Participants were less confident about beating a leading team and more confident about beating a trailing team, although they were unaware of the actual score during the depicted scenes. The present research is the first to show that in-game variations of naturally occurring nonverbal behavior can influence athletes’ confidence. This finding highlights the importance of research into nonverbal behavior in sports, particularly in relation to athletes’ confidence.
Gesehen am 17.08.2020